2005
DOI: 10.1103/physrevlett.95.157202
|View full text |Cite
|
Sign up to set email alerts
|

Reversing the Training Effect in Exchange BiasedCoO/CoBilayers

Abstract: We performed a detailed study of the training effect in exchange biased CoO/Co bilayers. High-resolution measurements of the anisotropic magnetoresistance (AMR) display an asymmetry in the first magnetization reversal process and training in the subsequent reversal processes. Surprisingly, the AMR measurements as well as magnetization measurements reveal that it is possible to partially reinduce the untrained state by performing a hysteresis measurement with an in-plane external field perpendicular to the cool… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
90
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 20 publications
13
90
2
Order By: Relevance
“…It is conceivable to think that this behaviour originates from sudden consecutive breaking of domain walls and consequent jumps from a pinning magnetic defect to the next one, whereas the smoother SFD observed when the magnetization switches back to the initial more stable orientation is related to a coherent rotation of the magnetic moments. This conjecture is consistent with similar conclusions derived from polarized neutron reflectivity, anisotropic magneto resistance and Kerr microscopy on CoO/Co bilayers [8,9].…”
Section: Joint European Magnetic Symposia 2012supporting
confidence: 80%
“…It is conceivable to think that this behaviour originates from sudden consecutive breaking of domain walls and consequent jumps from a pinning magnetic defect to the next one, whereas the smoother SFD observed when the magnetization switches back to the initial more stable orientation is related to a coherent rotation of the magnetic moments. This conjecture is consistent with similar conclusions derived from polarized neutron reflectivity, anisotropic magneto resistance and Kerr microscopy on CoO/Co bilayers [8,9].…”
Section: Joint European Magnetic Symposia 2012supporting
confidence: 80%
“…TE is typically observed in the magnetic hysteresis loop [7] which is recently reported in the MR-H curve of only two multilayer films, exhibiting EB effect [26,27]. In figure 5 typical signature of TE is illustrated at 5 K up to 5 successive cycles (λ).…”
Section: Training Effect In the Magnetoresistance Curvementioning
confidence: 97%
“…The bias field magnitude is not completely restored even after measuring loops perpendicular to the cooling field direction. 7 Here, the exchange anisotropy direction can be restored by winding the AF domain wall in the opposite direction through sample rotation.…”
Section: E508-2mentioning
confidence: 99%
“…Brems et al showed that applying fields perpendicular to the cooling field direction could counteract the training effects, even restoring the highly asymmetrical untrained hysteresis loop often found in trainable exchange biased samples. 7 In this paper, we study the effects of rotating the applied field on the exchange field direction of Co/ FeMn thin films. When the applied field is initially along the cooling field direction, the longitudinal loop has a maximum coercivity and the transverse loop is flat.…”
Section: Rotational Hysteresis Of the Exchange Anisotropy Direction Imentioning
confidence: 99%